Chemical and mechanical denudation rates in the Scott River catchment (Svalbard) during the summer season 2005 - Chmiel, Stanisław (1963- ); Bartoszewski, Stefan; Siwek, Krzysztof; Sposób, Joanna (Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, 2012)
artykuł z : Annales Universitatis Mariae Curie-Skłodowska. Sectio B, Geographia, Geologia, Mineralogia et Petrographia Vol. 67 (2012), 1, s. 93-107 streszcz. ang., pol. tyt. równol. w jęz. pol. : Denudacja chemiczna i mechaniczna w zlewni rzeki Scott (Svalbard) w sezonie letnim 2005 artykuł z : Annales Universitatis Mariae Curie-Skłodowska. Sectio B, Geographia, Geologia, Mineralogia et Petrographia Vol. 67 (2012), 1, s. 93-107 streszcz. ang., pol. tyt. równol. w jęz. pol. : Denudacja chemiczna i mechaniczna w zlewni rzeki Scott (Svalbard) w sezonie letnim 2005